A new method for calculation of majority carrier compensation in photovoltaics. (July 2015) - Zhang 张, Rumin 汝民; Liu 刘, Peng 鹏; Liu 刘, Dijun 迪军; Su 苏, Guobin 国斌
Abstract: In thin film solar cells, the semiconductor materials usually contain multiple impurity/defect states as donor or acceptor dopants. The local charge neutrality (LCN) condition determines the equilibrium Fermi (EF) level and concentration of electrons and holes. However, the equation of LCN is a transcendental equation of EF. It is impossible to find its analytical solution and we can only solve it by graphic or numerical method. A simple approximate graphic method (GM) used for estimation of majority carrier compensation of semiconductors with multiple donors and acceptors was proposed by Chin. By introducing the concept of ranking the dopants and the wrapping step function, dopants concentration and Fermi level could be obtained easily. In this paper, we analyze the graphic method and propose a new numeric graphic method (NGM) based on GM. In addition, comparison of NGM with NM and analytics of the accuracy of GM are presented. With numerical calculation, some procedures of GM extending the application of GM are improved.